A Study on the Mechanism of Female Participation in Rural Development of Yunnan on Their Capacity Building for Sustainable Development—Based on Cognitive, Emotional and Behavioural Perspectives - Gao, Suwei; Chen, Fan; Jiao, Jianyi; Zhang, Yangdan (Sustainability, 2024)
Rural women’s development is a problem related to current and future rural development, as well as the development of society as a whole. This paper takes the theory of planned behaviour as the basis, researches the mechanism of women’s rural development participation with the five indicators of participation behaviour, determines the indicators of rural development participation with the theory of informed behaviour; explores the relationship between the external environment, women’s family economy, human capital, social network and family roles and the persistent poverty and determines the indicators of sustainable and responsible capacity; and constructs a hypothetical model of the influence mechanism of rural development participation on the sustainable and responsible capacity building. It also constructs a hypothetical model of the influence mechanism of rural development participation on sustainable and responsible capacity building; conducts a questionnaire survey and collects data from women in the former poverty-stricken areas of Yunnan Province; empirically analyses and verifies the hypothetical model using structural equation modelling and, finally, puts forward policy recommendations, which will serve as important references for poor rural women to improve their sustainable development capacity. The results of the empirical study indicate that the impact of participation indicators on sustainability is that cognitive participation, emotional participation and behavioural participation of female subjects all positively affect sustainability. Cognitive participation affects behavioural participation, and increasing the cognitive level of rural development participation helps increase female rural development participation. Cognitive participation and affective participation also affect sustainability through behavioural participation but not exclusively through behavioural participation. In the analysis of the role of the external environment, the external environment directly affects the effect of rural development participation on the sustainable development capacity. According to the results of the data analysis, the external environment plays a significant positive moderating effect on the economic dimension and human capital in rural development participation and sustainable development capacity. The innovations of the study on the impact mechanism of rural women’s rural development participation on sustainable development capacity building are expanding the research perspective and research methods for studying rural women’s rural development participation, constructing a scale of rural development participation and sustainable development capacity building measurement indicators and exploring the impact mechanism of rural development participation on sustainable development capacity building of rural women in Yunnan.